THE CHARGE TRANSPORT AND PHOTOCONDUCTION MECHANISMS OF TiO2-BASED DYE SENSITIZED SOLAR CELL - Farooq, W. A.; Fatehmulla, Amanullah; Ocakoglu, K.; Yakuphanoğlu, Fahrettin (Ieee, 2012)
The charge transport and photoconduction mechanisms of the TiOrbased DSSC were analyzed under dark and illumination conditions. The effects of high and low electric fields on charge transport mechanism of the solar cell were investigated by current-voltage characteristics. It was found that the charge transport mechanism of the solar cell was controlled by the thermionic emission (TEC))at lower voltage and followed by space charge limited current (SCLC) at the higher voltages. The photovoltaic parameters of the solar cell were determined. It is evaluated that the charge transport mechanism is controlled by TEC and SCLC mechanisms, while photoconduction is controlled by supralinear recombination mechanism.
9th International Conference on High Capacity Optical Networks and Emerging/Enabling Technologies (HONET) -- DEC 12-14, 2012 -- Istanbul, TURKEY
Keywords: TiO2 photoanode; Photovoltaic properties; impedance spectroscopy